Acute Lymphoblastic Leukemia in a Man Treated With Fingolimod for Relapsing Multiple Sclerosis. (2nd March 2015) - Cohan, Stanley; Godwin, John; Gaedeke, Leah
A man with relapsing multiple sclerosis, treated with fingolimod 0.5 mg/d for 15 months, developed acute lymphoblastic leukemia and died 4 months after immune ablation and bone marrow allograft, from graft versus host disease. To our knowledge, this is the first case of acute lymphoblastic leukemia reported in a patient treated with fingolimod. Although no causal relationship can be established between fingolimod use and acute lymphoblastic leukemia risk in this single case, future surveillance for lymphatic cell malignancies in patients treated with fingolimod appears justified.